Yoruba art and language seeking the African in African art - Abiodun, Rowland 1941- (Cambridge University Press, 2014)
The Yoruba was one of the most important civilizations of sub-Saharan Africa. While the high quality and range of its artistic and material production have long been recognized, the art of the Yoruba has been judged primarily according to the standards and principles of Western aesthetics. In this book, which merges the methods of art history, archaeology, and anthropology, Rowland Abiodun offers new insights into Yoruba art and material culture by examining them within the context of the civilization's cultural norms and values and, above all, the Yoruba language. Abiodun draws on his fluency and prodigious knowledge of Yoruba culture and language to dramatically enrich our understanding of Yoruba civilization and its arts. The book includes a companion website with audio clips of the Yoruba language, helping the reader better grasp the integral connection between art and language in Yoruba culture
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Art, Yoruba; Yoruba language; Philosophy, Yoruba; Language and languages in art; Sprache; Kunst; Yoruba